The novel gene MIA2 acts as a tumour suppressor in hepatocellular carcinoma. Issue 2 (19th September 2007) - Hellerbrand, C; Amann, T; Schlegel, J; Wild, P; Bataille, F; Spruss, T; Hartmann, A; Bosserhoff, A-K
Abstract : Background: Melanoma inhibitory activity 2 (MIA2) is a novel gene of the MIA gene family. The selective expression of MIA2 in hepatocytes is controlled by hepatocyte nuclear factor (HNF) 1 binding sites in the MIA2 promotor. In contrast, in most hepatocellular carcinomas (HCC) MIA2 expression is down-regulated or lost. Aim: In this study we examined the regulation and functional role of MIA2 in hepatocancerogenesis. Methods and results: In HCC cell lines and tissues HNF-1 expression was lower than in primary human hepatocytes (PHH) and corresponding non-tumorous tissue, respectively, and correlated significantly with the down-regulation of MIA2 expression. Re-expression of HNF-1 in HCC cells reinduced MIA2 in HCC cells to similar levels as found in PHH. Further, MIA2 was re-expressed in HCC cell lines by stable transfection, and the generated cell clones revealed a strongly reduced invasive potential and proliferation rate in vitro. In line with these findings treatment of HCC cells with recombinant MIA2 inhibited proliferation and invasion. In nude mice MIA2 re-expressing HCC cells grew significantly slower and revealed a less invasive growth pattern. Immunohistochemical analysis of a tissue microarray containing HCC and corresponding non-cancerous liver tissue of 85 patients confirmed reduced MIA2 expression in HCC. Furthermore, MIA2 negative HCC tissue showed a significantly higher Ki67 labelling index and loss of MIA2 expression correlated significantly with more advanced tumour stages. Conclusion: This study presents MIA2 as an inhibitor of HCC growth and invasion both in vitro and in vivo, and consequently, as a tumour suppressor of HCC. Further, our findings indicate a novel mechanism, how loss of HNF-1 expression in HCC affects tumorigenicity via down-regulation of MIA2.